2012
DOI: 10.1136/thoraxjnl-2012-202678.282
|View full text |Cite
|
Sign up to set email alerts
|

P221 Temporal Trends in Severity and In-Hospital Mortality in Acute Hypercapnic Respiratory Failure (AHRF) at a Respiratory Ward-Based Non-Invasive Ventilation (NIV) Unit

Abstract: Wilcoxon rank sum test: p=0.03134; pH significantly lower in Period 2 Wilcoxon rank sum test: p=0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It has been shown that caring for a higher volume of NIV patients in ICU may develop local expertise and lead to better NIV outcomes [ 11 ]. We have seen similar effects of patient volume on local expertise when analysing temporal trends at a single, large ward-based NIV unit, recording that more severely ill acute hypercapnic respiratory failure patients are being treated with no significant change in mortality [ 12 ]. Ward-based NIV is consistently emerging as a sustainable tool to deal with acute exacerbations of COPD as well as other patients with ventilatory insufficiency leading to hospital admissions due to respiratory failure, who are now living longer with various comorbidities.…”
Section: Summary and Prospectmentioning
confidence: 99%
“…It has been shown that caring for a higher volume of NIV patients in ICU may develop local expertise and lead to better NIV outcomes [ 11 ]. We have seen similar effects of patient volume on local expertise when analysing temporal trends at a single, large ward-based NIV unit, recording that more severely ill acute hypercapnic respiratory failure patients are being treated with no significant change in mortality [ 12 ]. Ward-based NIV is consistently emerging as a sustainable tool to deal with acute exacerbations of COPD as well as other patients with ventilatory insufficiency leading to hospital admissions due to respiratory failure, who are now living longer with various comorbidities.…”
Section: Summary and Prospectmentioning
confidence: 99%
“…NIV for an exacerbation of chronic obstructive pulmonary disease (COPD) with acute hypercapnic respiratory failure is the most common scenario for ventilatory support in the pulmonary or the general ward [16]. A study by Dave et al even suggests that it is safe to ventilate patients with a pH of 7.6 outside of the ICU [17].…”
Section: Copd Exacerbationmentioning
confidence: 99%